Determining and detailing the structure model of the Earth’s crust in the East Vietnam Sea deep basin and adjacent areas using new seismic, OBS and gravity data - Tran , Tuan Dung; Tran, Tuan Duong; Nguyen, Quang Minh; Tran, Trong Lap; Nguyen, Ba Dai; Nguyen, Van Sang (Vietnam Journal of Marine Science and Technology, 2025)
The East Vietnam Sea deep basin and its adjacent areas exhibit a complex geological landscape. In many locations, the marine geological structure remains poorly understood due to insufficient data, the presence of a thick seawater layer, and the geopolitical sensitivities among the countries in the region. This paper employs 3D modeling techniques alongside the analysis of new seismic data, Ocean Bottom Seismometer (OBS) data, gravity measurements, and other relevant information to determine the Cenozoic basement, Moho surfaces, as well as the uplift and depression zones of the Earth’s crust. The findings of this study reveal several key insights: (1) In the oceanic crust area, the thickness of Cenozoic sediments is significantly greater, particularly along the sea floor spreading axis, with some locations reaching nearly 3 km; (2) This phenomenon is attributed to the gravity field along the spreading axis, which exhibits lower values compared to the surrounding areas, indicating a greater sediment thickness and lower sedimentary density; (3) The Moho surface in the oceanic crust is relatively flat but exhibits a rising trend along the spreading axis, reaching depths of up to 9 km in certain areas. Beneath the oceanic crust, the granite layer is absent, the basalt layer is very thin, and the upper mantle layer is elevated. These results have been validated using the available seismic and OBS data from the region. The newly constructed model represents a significant advancement beyond previous studies and provides a more detailed and accurate depiction of the Earth’s crust structure in the East Vietnam Sea, enhancing both the thickness values and the structural morphology of the fundamental boundary surfaces.